Duchenne muscular dystrophy - Chamberlain, Jeff (Henry Stewart Talks, 2007)
Introduction to duchenne muscular dystrophy (DMD), Dystrophin, the gene product of the DMD locus, Structure of dystrophin, The dystrophin glycoprotein complex, Gene therapy for DMD, Adeno-associated viral (AAV) vectors, Mini- and micro-dystrophins, Delivery of AAV vectors to muscles body-wide, Gene therapy of muscular dystrophy in mouse models using AAV, Alternative approaches to gene therapy of DMD